2017
DOI: 10.15255/cabeq.2016.831
|View full text |Cite
|
Sign up to set email alerts
|

Study on Some Properties of Calcium-dependent a -Amylase from Bacillus subtilis through Submerged Fermentation of Wheat Bran

Abstract: University of the Punjab new campus Lahore PakistanThis study reveals the production of α-amylase through Bacillus subtilis by submerged fermentation of wheat bran as a substrate. Various conditions were optimized and maximum production was observed at initial medium pH of 7.0, incubation temperature of 35 °C with agitation speed of 140 rpm for 48 h of fermentation period. Peptone, ammonium sulphate and soluble starch favored enzyme production as nitrogen and carbon source, respectively. The crude α-amylase wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Commonly, bacterial α‐amylases are known to be stable in the presence of calcium ion. Indeed, Irfan () indicated that calcium played a key role for amylases stability and activity. Few studies reported that amylases were Ca 2+ ‐independent (Sajedi et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, bacterial α‐amylases are known to be stable in the presence of calcium ion. Indeed, Irfan () indicated that calcium played a key role for amylases stability and activity. Few studies reported that amylases were Ca 2+ ‐independent (Sajedi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Irfan (2017) indicated that calcium played a key role for amylases stability and activity. Few studies reported that amylases were Ca 2+ -independent (Sajedi et al, 2005).…”
Section: Influence Of Metallic Ions On Amy586mentioning
confidence: 99%
“…Bacillus subtilis BI19 and Bacillus licheniformis B4-423 had the highest crude-amylase enzyme activity at pH 6.0 and pH 5.0, respectively (Dash et al, 2015;Wu et al, 2018). The optimum pH of α-amylase was reported 8.5 which was produced from B. subtilis by using wheat bran as substrate in submerged fermentation (Irfan et al, 2016). The optimal activity of α-amylase produced by B. subtilis was also observed at pH 6.0 (Özdemir et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Amylase assay. Activity of α-amylase was calculated using amylase assay conditions [8]. Reaction mixture having 0.5 mL of crude enzyme and 0.5mL of 1% starch solution (pH 7) incubated at 60°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%